Teksttype og polyfoni - Fløttum, Kjersti (HERMES - Journal of Language and Communication in Business, 1998)
There is a general scepticism as to definitions of text types based on determined lin-guistic criteria. The subject of this article is to show how it is possible to strengthen the linguistic basis of text typologies. After a description of the evolution of text typology from Werlich (1976) via van Dijk (1980) to Adam (1992), linguistic polyphony is presented as a contribution to a linguistic foundation of Adamís prototypical typology. It is shown how the polyphonic structure can describe, make explicit and explain ty-pological text features.